1992
DOI: 10.1128/jb.174.14.4736-4745.1992
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the rfaB, rfaI, rfaJ, and rfaS genes of Escherichia coli K-12 and their roles in assembly of the lipopolysaccharide core

Abstract: Analysis of the sequence of a 4.1-kb rfa region downstream from rfaP revealed four genes. The first of these encodes a basic protein of 36,730 Da and does not correspond to any known rfa gene. It has been designated rfaS. The second gene was identified as rfaB on the basis of its ability to complement a Salmonella typhimurium rfaB mutant and encodes a 42,060-Da protein. The third and fourth genes encode proteins of 39,423 and 36,046 Da which are strongly homologous to the RfaI and RfaJ proteins of S. typhimuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
110
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(113 citation statements)
references
References 21 publications
3
110
0
Order By: Relevance
“…From the genes flanking acs operons, cmcAX, ccpAX, bglxA, bcsX, and bcsY have been previously shown to contribute to cellulose production in closely related species (26,33,34). We found two other, stand-alone copies of bglxA from the genome (genomic positions 517401-519440 and 3029825-3032221), and also identified genes close to acs2 that are associated with extracellular matrix formation (kpsC, kpsS, and rfaB) and may play a role in cellulose productivity (35,36). Finally, to determine whether the iGEM strain can fix atmospheric nitrogen similar to G. diazotrophicus, we searched its genome for genes associated with nitrogen fixation.…”
Section: Resultsmentioning
confidence: 80%
“…From the genes flanking acs operons, cmcAX, ccpAX, bglxA, bcsX, and bcsY have been previously shown to contribute to cellulose production in closely related species (26,33,34). We found two other, stand-alone copies of bglxA from the genome (genomic positions 517401-519440 and 3029825-3032221), and also identified genes close to acs2 that are associated with extracellular matrix formation (kpsC, kpsS, and rfaB) and may play a role in cellulose productivity (35,36). Finally, to determine whether the iGEM strain can fix atmospheric nitrogen similar to G. diazotrophicus, we searched its genome for genes associated with nitrogen fixation.…”
Section: Resultsmentioning
confidence: 80%
“…CpsL displayed significant homology to only one protein : WaaS from the LPS biosynthetic pathway of E. coli. A specific function has not been assigned to WaaS, however it has been suggested that it may act as an accessory protein required for the assembly of outer-core oligosaccharide, interacting either with glycosyltransferases or with the inner core LPS moiety (Pradel et al, 1992). Alternatively, Heinrichs et al (1998) speculate that WaaS may be a rhamnosyltransferase, thus CpsL may be a rhamnosyltransferase.…”
Section: Fig 2 Hydrophobicity Plots Of Cpse and Cpse Proteins Frommentioning
confidence: 99%
“…Restriction fragments from E. coli K-12 carrying genes rfaG, rfaP, and rfaB are capable of efficiently complementing corresponding mutations in S. typhimurium (16,17). The protein products of the rfaI and rfaJgenes of E. coli K-12 and S. typhimurium share substantial regions of homology, particularly surprising in view of the fact that they are thought to be sugar transferases of different specificities, and restriction fragments from E. coli K-12 which include both rfaI and rfaJ can efficiently complement either rfaI or rfaJ mutations of S. typhimunium (18).…”
mentioning
confidence: 99%